O61: TEXTBOOK SURGICAL OUTCOMES IN OESOPHAGO-GASTRIC CANCER: THE INFLUENCE OF NATIONAL KEY PERFORMANCE INDICATORS. (27th April 2021) - Al Azzawi, M; Bolger, JC; Bolger, EM; Whooley, J; Allen, J; Trench, L; Downey, E; Arumugasamy, M; Robb, WB
Abstract: Introduction: High quality surgery remains the cornerstone of treating oesophago-gastric malignancy. Recent work from the Dutch Upper-gastrointestinal Cancer Audit (DUCA) have defined ten surgical and perioperative 'textbook' parameters that correlate with improved overall survival. The aim of this project was to examine the proportion of patients attaining 'textbook' outcomes for oesophagectomy and gastrectomy in our unit before and after the introduction of national key performance indicators (KPIs). Method: A retrospective review of all oesophagectomies and gastrectomies from January 2010 until June 2019 was performed. Clinical, pathological, perioperative, morbidity and mortality outcomes were recorded. 10 'textbook' parameters were studied pre- and post-KPI introduction. Result: 269 and 284 patients underwent oesophagectomy and gastrectomy respectively, 167 pre-KPI and 386 post-KPI. There were no significant differences in age (67.6 vs 66.4 years, p=0.6), gender (71% male, 29% female vs 68% male, 22% female, p=0.48), ASA grade (p=0.6) or tumour stage (p=0.37) pre- and post-KPI. In the pre-KPI era, 28/167 (17%) patients achieved all ten textbook parameters, compared with 157/386, (41%, p=0.001) post-KPI. This compares favourably to DUCA 'textbook' data. There was an improvement in adequate lymphadenectomy (56% vs 83%, p=0.002), a reduction in margin positivity (21% vs 7%, p= 0.001) and peri-operative mortality (6% vs 2%, p=0.03) post-KPI. Conclusion: There has been a significant improvement in perioperative outcomes in esophagectomy following the introduction of national KPIs in our unit. The number of patients achieving 'textbook' outcomes is comparable with international standards. The identification of textbook parameters allows further focus for future quality improvement initiatives. Take-home message: National KPIs improve peri-operative outcomes in oesophago-gastric cancer.